PENGGUNAAN METODE MIND MAPPING UNTUK MENINGKATKAN KEMAMPUAN MEMAHAMI BACAAN SISWA KELAS XI SMA ADI SUCIPTO KUBURAYA - Eka Kurnia Victory; Lily Thamrin; Bun Yan Khiong (Universitas Tanjungpura, 2022)
At present, many schools already have Chinese courses and it has become one of the compulsory courses. In the process of learning Chinese at school, there are certain abilities that must be mastered, such as reading, memorizing words, and understanding the meaning of the text. By reading we gain information and strengthen our comprehension. In practice, it is usually the teacher who gives the student a certain time to read what is to be explained. However, students face some internal and external problems in the process of learning Chinese. In order to improve students' ability to learn Chinese, the author used the mind mapping method to conduct research on the second grade students of Kubu Raya Adi Sucipto High School. The purpose of this research is to improve the comprehension ability of the second grade students of Kubu Raya Adi Sucipto high school in Chinese text by applying the method of mind mapping. There are two types of research methods used, namely pre-test and post-test. This study was conducted from April 19, 2021 to May 17, 2021. According to the predicted results, the average pre-test score was 34%. The post-test results showed that the average score was 84.67%. This proves that the mind mapping method can improve students' ability to understand Chinese texts.